Basic kitchen preparation [videorecording] - Culinary Institute of America ([Hyde Park, N.Y.] Culinary Institute of America, 2006)
Everything you do in a kitchen is made up of several small steps. Some of these steps are done every day, while others are done only once in awhile. None of these steps will lead you to a finished product, but they do give you something that will be used in a larger recipe. It's all about the basics, and correct preparation is the key.
DVD
Producer/Director, Project Manager, Philip Miller ; Videography, Skip Thela, Maria Renz.
Keywords: Cooking; Cooking (Bread); Cooking (Dairy products); Cooking (Vegetables); Food handling